ORGANIZATION OF SELF-DEPENDENT COGNITIVE ACTIVITY OF PUPILS IN PHYSICS USING INFORMATION TECHNOLOGIES (Journal of Information Technologies in Education (ITE), 2010)
The article deals with opportunities of using information technologies to organize self-dependent cognitive activity of pupils in physics.
Keywords: information technologies; self-dependent cognitive activity; the forms of organization of self-dependent cognitive activity